1999
DOI: 10.1159/000017377
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Amino Acid Neurotransmitters during Mouse Cerebellar Neurogenesis and in Histotypic Cerebellar Cultures

Abstract: The variation in the levels of excitatory (glutamate and aspartate) and inhibitory (GABA, glycine and taurine) neurotransmitters during neurogenesis in mouse cerebellum, from embryonic day (E) 15 until the young adult stage, was analyzed by high-pressure liquid chromatography. Between E15 and E21, high contents of GABA, glutamate and aspartate were detected, with the GABA levels approximately 2- to 3-fold higher than those of glutamate and aspartate. After birth, the levels of GABA remained high during the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 67 publications
(84 reference statements)
5
17
0
Order By: Relevance
“…In addition to the coexistence of Glu and GABA, consistent with previous studies reporting age-dependent changes in multiple neurotransmitter systems in brain tissue (36,37), we also found that the concentrations of amino acids neurotransmitters, including Glu and GABA, in single cells decrease with age. Interestingly, we observed that the correlation among single-cellular Gln, Glu, and GABA is much more significant in infants than that in children or adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition to the coexistence of Glu and GABA, consistent with previous studies reporting age-dependent changes in multiple neurotransmitter systems in brain tissue (36,37), we also found that the concentrations of amino acids neurotransmitters, including Glu and GABA, in single cells decrease with age. Interestingly, we observed that the correlation among single-cellular Gln, Glu, and GABA is much more significant in infants than that in children or adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…( Changes in the Levels of Cytoplasmic Chemical Constituents at Different Stages of Brain Development. Previous reports suggest that the levels of amino acid neurotransmitters tend to decrease with age (36,37). Using single-cell MS, we investigated this idea at the single-neuron level.…”
Section: Concentrations Of Cytoplasmic Chemical Constituents In Singlmentioning
confidence: 99%
“…Comparing our data with those from Weiss et al, who also used high temporal resolution, our data correlated better with concentrations measured ex vivo by high-performance liquid chromatography during brain maturation in the thalamus and with concentrations in humans, (own unpublished data) [11,21,25,26]. For instance, in our study, the concentrations of tCr, tNAA, and Glx show a steady increase in the developing brain and reach a plateau when the brain maturation is finished.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to our in vivo MRS study, HPLC analysis indicated that the taurine content in the thalamus was twofold lower at D9 and D11 compared with those at D7 and P15 and at D19, twofold higher compared with the cerebellum and olfactory bulb. Comparison of ex vivo HPLC levels with those observed in vitro, in histotypic cerebellar cultures, demonstrated a content which was fivefold lower in vitro than ex vivo (13), suggesting that the high proportion of endogenous taurine observed in cerebellum could come from an extrinsic origin. In the rat brain, specific antibodies of high-affinity Tau transporters showed a predominant localisation in the cerebellum, in the neuronal Purkinje cell and in Bergmann glial cells (15).…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the Tau content in thalamus is twofold higher than in other structures. When the Tau concentration was measured ex vivo by high-performance liquid chromatography (HPLC) during brain maturation in these three regions (12)(13)(14), its values decreased between birth and the young adult stage. Similarly to our in vivo MRS study, HPLC analysis indicated that the taurine content in the thalamus was twofold lower at D9 and D11 compared with those at D7 and P15 and at D19, twofold higher compared with the cerebellum and olfactory bulb.…”
Section: Discussionmentioning
confidence: 99%